1994
DOI: 10.1073/pnas.91.11.5187
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic fibronectin peptides interrupt inflammatory cell infiltration in transforming growth factor beta 1 knockout mice.

Abstract: Pronounced mononuclear leukocyte (MNL) inflitration occurs in multiple organs of mice homozygous for a transforming growth factor 131 (TGF-fl) loss-of-ftunction gene mutation [TGF-1l1 (-/-)J, followed by cachexia and eventually death. Consistent with the Increased leukocyte adhesion and tissue infiltration, MNUs isolated from spleen, thymus, and peripheral blood of symptomatic TGF-I81 (-/-)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…It is known that activated T cells exhibit enhanced adhesion to endothelial cells (61), that TGF-␤1 inhibits the adhesion of neutrophils and T cells to endothelial cells (62,63), and that TGF-␤1 affects platelet integrin activity (5). These facts are consistent with splenocytes from Tgfb1 Ϫ/Ϫ mice exhibiting enhanced adhesiveness to endothelial cells (28). Since LFA-1 is up-regulated on CD3 ϩ T cells in Tgfb1 Ϫ/Ϫ mice, and since anti-LFA-1 treatment rescues these mice from inflammatory autoimmune disease, it is reasonable to speculate that Tgfb1 Ϫ/Ϫ T cells adhere to endothelial cells and extravasate into peripheral organs more rapidly in Tgfb1 Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 76%
“…It is known that activated T cells exhibit enhanced adhesion to endothelial cells (61), that TGF-␤1 inhibits the adhesion of neutrophils and T cells to endothelial cells (62,63), and that TGF-␤1 affects platelet integrin activity (5). These facts are consistent with splenocytes from Tgfb1 Ϫ/Ϫ mice exhibiting enhanced adhesiveness to endothelial cells (28). Since LFA-1 is up-regulated on CD3 ϩ T cells in Tgfb1 Ϫ/Ϫ mice, and since anti-LFA-1 treatment rescues these mice from inflammatory autoimmune disease, it is reasonable to speculate that Tgfb1 Ϫ/Ϫ T cells adhere to endothelial cells and extravasate into peripheral organs more rapidly in Tgfb1 Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 76%
“…Although the underlying instigatory mechanism of the inflammatory pathology is not known, the ability to modulate the inflammatory sequelae by blocking recruitment and migration (30,31), activation (8,32), and, as demonstrated here, signal transduction, by targeting either NF-B activation or TLR4 expression, highlights the complexity of the inflammatory phenotype of the TGF-␤1 null mouse. However, in the absence of any identifiable pathologic agent, the initiator of these events remains a mystery.…”
Section: Discussionmentioning
confidence: 99%
“…Null mice treated with normal rat IgG experienced the typical wasting syndrome which ensued at ϳ12-14 days of age (data not shown and Ref. 15) and died by 15-19 days. In comparison, mice treated with anti-IFN-␥ maintained a constant weight or increased in weight, and life span was extended by nearly 2-fold to days 29 -32 ( p ϭ 0.004 as compared with IgG-treated null mice) (Fig.…”
Section: Treatment With Anti-ifn-␥ Increases the Life Span Of The Tgfmentioning
confidence: 99%
“…Infiltration of lymphocytes and macrophages, particularly in heart and lungs, is associated with cardiopulmonary failure. Increased MHC Ag, cytokines, adhesion molecules, and autoantibody expression suggest an autoimmune origin of the pathological lesions (12)(13)(14)(15)(16)(17). Recent studies have shown enhanced expression of IFN-␥ RNA before the appearance of inflammatory lesions in TGF-␤1 null mice (13), consistent with disruption of immunoregulatory circuits in the absence of TGF-␤1.…”
Section: Dysregulation Of Ifn-␥ Signaling Pathways In the Absence Of mentioning
confidence: 99%